The effect of anemia free-club model (CBA) application and giving of blood supplementary tablets (TTD) on knowledge, attitudes, and hemoglobin levels in anemic teenage girls of Senior High School - Reni Zuraida; Susianti Susianti; Dian Isti Angraini; Bayu Anggileo Pramesona; Wido Gamani; Catur Ariwibowo; Zakiah Zakiah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Introduction: The prevalence of anemia among teenage girls in senior high schools in Lampung Province is still quite high. A more comprehensive coping model is needed to improve this situation, such as applying the CBA (Anemia Free Club) model, which consists of nutrition education and the supervisory role of mothers and teachers. This study aims to analyze the effect of applying the CBA model and administering blood supplementary tablets on knowledge, attitudes and hemoglobin levels in anemic teenage girls of high school students in South Lampung Regency. Methodology: Quasi-experimental research with a non-randomized control group pretest–posttest design. The research was conducted in February-May 2022 using the consecutive sampling technique by dividing into two groups: the intervention group of senior high school and the control group of senior high school. The Anemia Free-club model was applied for anemic teenage girls, and supplementary tablets were given for six weeks. The analytical test used was the paired t-test using the SPSS program and was considered to have a significant effect if p less than 0,05. Results: After implementing the Anemia Free-club model and giving iron supplements, in the intervention group, there was an increase in the nutrition knowledge (up 45.33 points), the nutritional attitude (up 9.8 points) and the Hb level (up 1,06 mg/dL). Conclusion: It showed a significant effect between the application of the CBA model and the administration of blood supplementary tablets on nutritional knowledge, nutritional attitudes, and Hb levels (p less than 0,05) in the intervention group.